Hubungan Penggunaan Smartphone Sebelum Tidur terhadap Kualitas Tidur Mahasiswa S1 Ilmu Keperawatan UNISSULA - Tia Nava Utari Tanjung; Dinda Syahfitri Ramadhani; Ajizah Sapitri Siregar; Siti Aisyah (Pusat Riset dan Inovasi Nasional, 2026)
The increasing use of smartphones among university students has become part of their daily lifestyle and may lead to various impacts, one of which is affecting sleep quality. Using smartphones before bedtime can cause the brain to remain highly active, disrupt the body’s internal clock, and result in shorter and less restful sleep. This study aims to examine how smartphone use before bedtime affects the sleep quality of university students. This study employed an analytic observational design with a cross-sectional approach. The study population consisted of 529 active undergraduate students in the Nursing Science program, with a sample size of 230 respondents determined using the Slovin formula. Data were collected using a questionnaire on smartphone use before bedtime and a sleep quality questionnaire. Data analysis included univariate analysis to describe respondents’ characteristics and bivariate analysis using the Spearman Rank correlation test. The results showed that most participants were 21 years old and female. The majority of students frequently used smartphones before bedtime and had poor sleep quality. The correlation test results indicated a significant relationship between smartphone use before bedtime and students’ sleep quality. The correlation coefficient was r = 0.528 with p < 0.05, indicating a moderately strong relationship. The more frequently students used smartphones before bedtime, the poorer their sleep quality. There is a significant association between smartphone use before bedtime and students’ sleep quality; therefore, education and regulation of smartphone use at night are necessary to improve students’ sleep quality.